DEVELOPMENT OF DIGITAL SOCIAL STUDIES LEARNING MATERIALS BASED ON DAYAK DEAH LOCAL WISDOM TO INCREASE ENVIRONMENTAL AWARENESS - Dewicca Fatma Nadilla; Herry Porda Nugroho Putro; Wisnu Subroto; Ilham Galih Pambudi (JURNAL SOCIUS, 2026)
This study aims to develop digital Social Studies (IPS) learning materials based on the local wisdom of the Dayak Deah community, particularly the Tawas Jaa tradition, and to examine their feasibility and effectiveness in enhancing junior high school students’ environmental awareness. The novelty of this study lies in the integration of the ecological values embedded in the Tawas Jaa tradition of the Dayak Deah community into Social Studies learning materials in the form of a digital storybook, which has not previously been developed within local wisdom based Social Studies learning.The study employed a Research and Development (R&D) approach using the 4D development model, which consists of the stages of define, design, develop, and disseminate. The research subjects included 27 seventh-grade students of SMPN 2 Upau as the experimental group and 25 students as the control group. Data were collected through observation, questionnaires, and environmental awareness tests, and were analyzed using descriptive and inferential statistics.The results indicate that in the define stage, students’ environmental awareness was still predominantly reflected in the knowledge dimension, while the attitude and behavioral dimensions remained at moderate to low levels. The design stage produced a prototype of a digital storybook that contextually integrates the ecological values of the Tawas Jaa tradition into Social Studies learning. In the develop stage, expert validation showed a very high level of feasibility with an average score of 85%. The limited trial results indicated very positive student responses, with an average score of 84% in terms of usability, attractiveness, and usefulness.The paired sample t-test analysis revealed a significant difference between the pre-test and post-test scores of the experimental group (p < 0.05), with a greater improvement compared to the control group. The study concludes that the digital Social Studies learning materials based on the Dayak Deah Tawas Jaa tradition meet the criteria of validity, practicality, and effectiveness in improving students’ environmental awareness. These findings suggest that integrating local wisdom into digital learning media can significantly contribute to strengthening environmental awareness in Social Studies learning.